2020
DOI: 10.1111/gcb.15039
|View full text |Cite
|
Sign up to set email alerts
|

Will coral reef sponges be winners in the Anthropocene?

Abstract: Recent observations have shown that increases in climate change‐related coral mortality cause changes in shallow coral reef community structure through phase shifts to alternative taxa. As a result, sponges have emerged as a potential candidate taxon to become a “winner,” and therefore a numerically and functionally dominant member of many coral reef communities. But, in order for this to occur, there must be sufficient trophic resources to support larger populations of these active filter‐feeding organisms. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 91 publications
(226 reference statements)
0
44
1
Order By: Relevance
“…However, climate change-driven increases in ocean temperatures can cause secondary physical changes in the water column such as stratification and changes in the mixed layer depth resulting in lower nutrients and net primary production. A reduced or altered food supply, especially in combination with an increased metabolism could cause the benthic fauna to starve (Sweetman et al 2017;Lesser and Slattery 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, climate change-driven increases in ocean temperatures can cause secondary physical changes in the water column such as stratification and changes in the mixed layer depth resulting in lower nutrients and net primary production. A reduced or altered food supply, especially in combination with an increased metabolism could cause the benthic fauna to starve (Sweetman et al 2017;Lesser and Slattery 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that sponges might be increasing in abundance as consequence of climate change and anthropogenic stressors such as eutrophication, overfishing or sedimentation (Loh et al 2015;Biggerstaff et al 2018;Chaves-Fonnegra et al 2018). Whereas the temporal persistence of sponge reefs and their functioning is still unclear and the subject of much current discussion (Lesser and Slattery, 2020;Pawlik and McMurray, 2020), an impeding limitation in hitherto existing studies is potentially the consideration of sponge reefs as a homogeneous entity. In fact, sponge species display marked divergence in their morphotypes and life histories, with some encrusting sponges such as Terpios hoshinota displaying turnover rates of months, whereas barrel sponges live thousands of years (Yomogida et al 2017;McGrawth et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that sponges in coral reefs are more resilient than corals to the rise in seawater temperatures, and some argue that they may outcompete corals in such cases (Bell et al, 2013(Bell et al, , 2018. Others, however, claim that synergistic effects with additional factors (e.g., ocean acidification, reduction in nutrients, and pollution) will adversely affect their populations (Bennett et al, 2017;Lesser and Slattery, 2020). The effect of rising temperatures may be direct, by causing stress to the sponges themselves -evident by the expression of heat-shock protein (Itskovich et al, 2018), or indirect, by affecting the composition of the microbiota inhabiting the sponges (Webster et al, 2008a,b), in some cases creating favorable conditions for opportunistic or pathogenic microorganisms (Webster et al, 2008a;Laffy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%